Muscle Eccentric Contractions Increase in Downhill and High-Grade Uphill Walking - Hu, Xiao; Pickle, Nathaniel T.; Grabowski, Alena M.; Silverman, Anne K.; Blemker, Silvia S. (Frontiers in Bioengineering and Biotechnology, 2020)
In Duchenne muscular dystrophy (DMD), one of the most severe and frequent genetic diseases in humans, dystrophic muscles are prone to damage caused by mechanical stresses during eccentric contractions. Eccentric contraction during walking on level ground likely contributes to the progression of degeneration in lower limb muscles. However, little is known about how the amount of muscle eccentric contractions is affected by downhill/uphill sloped walking, which is often encountered in patients’ daily lives and poses different biomechanical demands than level walking. By recreating the dynamic musculoskeletal simulations of downhill (-9°, -6°, and -3°), uphill (+3°, +6°, and +9°) and level walking (0°) from a published study of healthy participants, negative muscle mechanical work, as a measure of eccentric contraction, of 35 lower limb muscles was quantified and compared. Our results indicated that downhill walking overall induced more (32% at -9°, 19% at -6° and 13% at -3°) eccentric contractions in lower limb muscles compared to level walking. In contrast, uphill walking led to eccentric contractions similar to level walking at low grades (+3° and +6°), but 17% more eccentric contraction at high grades (+9°). The changes of muscle eccentric contraction were largely predicted by the changes in both joint negative work and muscle coactivation in sloped walking. As muscle eccentric contractions play a critical role in the disease progression in DMD, this study provides an important baseline for future studies to safely improve rehabilitation strategies and exercise management for patients with DMD and other similar conditions.